2015
DOI: 10.1038/srep14223
|View full text |Cite
|
Sign up to set email alerts
|

Structural models of intrinsically disordered and calcium-bound folded states of a protein adapted for secretion

Abstract: Many Gram-negative bacteria use Type I secretion systems, T1SS, to secrete virulence factors that contain calcium-binding Repeat-in-ToXin (RTX) motifs. Here, we present structural models of an RTX protein, RD, in both its intrinsically disordered calcium-free Apo-state and its folded calcium-bound Holo-state. Apo-RD behaves as a disordered polymer chain comprising several statistical elements that exhibit local rigidity with residual secondary structure. Holo-RD is a folded multi-domain protein with an anisome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
50
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

5
2

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 49 publications
5
50
0
Order By: Relevance
“…These data have direct implications for CyaA secretion. We previously suggested that in the low calcium environment of the bacterial cytosol, RD adopts disordered conformations favorable for transport through the type 1 secretion machinery and folds upon binding calcium in the extracellular, calcium-rich environment (4,32,34,39,41,42). Our present data now extend this model to the full-length CyaA toxin.…”
Section: Relativesupporting
confidence: 73%
See 1 more Smart Citation
“…These data have direct implications for CyaA secretion. We previously suggested that in the low calcium environment of the bacterial cytosol, RD adopts disordered conformations favorable for transport through the type 1 secretion machinery and folds upon binding calcium in the extracellular, calcium-rich environment (4,32,34,39,41,42). Our present data now extend this model to the full-length CyaA toxin.…”
Section: Relativesupporting
confidence: 73%
“…Finally, the C-terminal 701 residues (1006-1706) correspond to the cell receptor-binding domain, RTX domain (RD), which harbors ;40 copies of a glycine-and aspartate-rich nona-peptide repeat, characteristic of the RTX bacterial cytolysins. In the absence of calcium, these RTX motifs are intrinsically disordered but undergo a disorder-to-order transition upon calcium binding (4,(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42). The RTX motifs themselves constitute the primary sites of calcium binding within the protein (3,31,43,44).…”
mentioning
confidence: 99%
“…MEMHDX was evaluated using our recently published differential HDX-MS dataset generated with the C-terminal R epeat-in-toxin D omain (RD, 701 residues) of the CyaA toxin (O'Brien et al , 2015). Briefly, we used HDX to identify and locate secondary structural elements in the intrinsically disordered Apo-RD protein, and followed its transition to a more compact and folded state upon calcium binding.…”
Section: Resultsmentioning
confidence: 99%
“…peptide 395–401). Results generated with MEMHDX were compared with those manually obtained for RD (O'Brien et al , 2015). Excellent agreement was observed between the automated software and the manual approach.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation